Experimental study on the evolution characteristics of gas pressure field for true triaxial cyclic mining - Geng, Jiabo; Liu, Jiangtong; Zeng, Gaoxiong; Zhang, Dongming; Guo, Zhigguo; Xu, Jiang (Frontiers in Earth Science, 2023)
The evolution characteristics of coal seam strain and gas pressure in circular mining were explored by conducting physical simulation tests on the influence of cyclic stress on coal seam parameters under different initial gas pressures using a large true triaxial physical simulation test rig. The evolution characteristics of gas pressure and coal seam strain with the number of cycles and gas pressure were discussed. The test results showed that during cyclic loading and unloading, the coal seam is cracked under stress and new cracks are generated, and the new fractures cause the overall pressure of the coal seam methane to decrease by adsorbing more free gas. In the loading stage, the coal skeleton is squeezed by stress, which causes the space of coal seam pores and cracks to shrink, the free gas in the pores and fractures of the coal seam is extruded, and the strain and gas pressure of the coal seam increase with the increase of stress. In the unloading stage, the reduction of stress leads to the coal skeleton tending to return to its initial state, the free gas in the pores is transported and enriched into the fractures of the coal seam, and the strain and gas pressure of the coal seam are gradually reduced. With the increase of the number of cycles, the damage of the coal seam increases and deformation occurs, the increasing amplitude of gas pressure gradually increases during loading, and the decreasing amplitude of gas pressure gradually decreases when unloading, and the closer the distance from the pressurized boundary, the greater the amplitude change. Under different initial gas pressure conditions, the greater the initial gas pressure, the greater the increasing amplitude of gas pressure and the smaller the decreasing amplitude.